Penerapan Teori Polya Dalam Menyelesaikan Masalah Matematika di SD /MI - Nadia Syahfitri; Rora Rizky Wandini (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Mathematics lessons are lessons that are able to provide students with insight into gaining knowledge systematically or how to solve a mathematical problem. One of the goals of learning mathematics is to develop problem solving abilities. This indicates that problem solving is a very important ability to hone in learning mathematics. The method used is literature study or literature review. The study sources are in the form of reference books, published scientific journals, and references on websites accessed via the internet. Theoretical references obtained through literature study research will be used as the basic foundation and main tool for further practice which will be followed up with field research. Polya's theory is a systematic approach to solving mathematical problems which consists of four main steps, namely understanding the problem, planning a solution, implementing the plan, and checking again. This theory has been applied in various mathematics learning contexts, such as in analyzing the difficulty of solving mathematical problems on various materials and levels of difficulty.